Optimal design of a single-input parallel DC-DC Converter designed by switched capacitor techniques - Eguchi, Kei; Pongswatd, Sawai; Tirasesth, Kitti; Sasaki, Hirofumi; Inoue, Takahiro (My University, 2010)
In the design of parallel-connected power converters, theoretical analysis to clarify the influence of process fluctuation is important, because the characteristic of a converter which consists of many circuit components is strongly influenced by the fluctua-tion of those components. Concerning parallel-connected switched-capacitor (SC) DC-DC converters, 1. the optimal setting of a duty factor to achieve best efficiency and 2. the change in characteristics caused by fluctuation of circuit components are analyzed in this paper. The validity of the theoretical analyses is confirmed by SPICE simulations and experiments. The results of this study are as follows: 1. The optimal setting of duty fac-tor D can be derived by the proposed theoretical formulas, because the theoretical results correspond well with the simulated results. 2. The fluctuation of on-resistances affects power efficiency in proportion to the decrease of output load RL. The value of the total SC resistance is important in power efficiency η, for example, an increase of 20 % in the total SC resistance causes a decrease of 2.2 % in efficiency when RL = 5ω. 3. When fluctuation of input voltages is caused, the influence on power efficiency η increases ac-cording to output load R L. 4. In the case of the fluctuation of capacitance, the influence of ripple factor R depends on fluctuating directions of capacitances. © 2010 ISSN.
Keywords: DC-DC converters; Fluctu-ation analysis; Parallel-connected converters; Power converters; Power efficiency; Switched capacitor circuits